2015
DOI: 10.1039/c5ay02389k
|View full text |Cite
|
Sign up to set email alerts
|

Detection and imaging of fatty plaques in blood vessels using functionalized carbon dots

Abstract: Risk of developing atherosclerosis is proportional to blood cholesterol level which in turn eventually leads to heart attack. Since a large number of asymptomatic young people have evidence of atherosclerosis it is highly necessary to diagnose it at the earliest. This communication depicts a simple method to visualize cholesterol deposits using digitonin (DG) conjugated carbon dots (CDs). Physico chemical characterizations and preliminary blood compatibility evaluation of the functionalized CDs (CDDG) were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They observed that the CDDG was capable of selective binding to cholesterol as they were evidently able to make images from cholesterol doped polymer films and tissues with heavy fatty plaques suspended in blood serum. Moreover, their obtained findings suggest that the CDDG is usable to selectively detect cholesterol in solution [73]. Sun et al have studied the detection of cholesterol by nanoprobe.…”
Section: Biochemical Detectionmentioning
confidence: 99%
“…They observed that the CDDG was capable of selective binding to cholesterol as they were evidently able to make images from cholesterol doped polymer films and tissues with heavy fatty plaques suspended in blood serum. Moreover, their obtained findings suggest that the CDDG is usable to selectively detect cholesterol in solution [73]. Sun et al have studied the detection of cholesterol by nanoprobe.…”
Section: Biochemical Detectionmentioning
confidence: 99%